Digital competency framework in digital technology towards future industrial revolution in Malaysia - Ismail, Asnidatul Adilah; Hassan, Razali; Ahmad, Azura (Universiti Teknologi MARA, Kedah, 2024)
This study aimed to identify the digital competency domains and elements necessary for IT graduates to succeed in the future job market in Malaysia and develop a digital competency framework specifically for future IT graduates. The research used a quantitative approach, using survey as a data collection method, and applied exploratory factor analysis (EFA) for pilot research to five polytechnics that offered information technology programs. The results of the EFA were carried out to actual data collection to ten polytechnics and were validated using confirmatory factor analysis (CFA). The study found the need for a Digital Competency Framework for Polytechnic IT Graduates to guide and standardize their level of competence. The framework covers four domains of digital competencies: Personal Effective Competencies, Functional Competencies, Essential Competencies, and 4IR Competencies. It consists of 15 elements, and quantitative analysis showed that two domains were at a high level of digital competence, and one was at an average level. The CFA confirmed that the four dimensions of the framework were significantly represented by their domains and elements. The research provides valuable insights into the necessary digital competencies required for future IT graduates and contributes to the development of a more robust educational system that can prepare students for the challenges of the fourth industrial revolution (IR4.0) in Malaysia.